DNA Damage Responses and Oxidative Stress in Dyskeratosis Congenita - Pereboeva, Larisa; Westin, Erik; Patel, Toral; Flaniken, Ian; Lamb, Lawrence; Klingelhutz, Aloysius; Goldman, Frederick (PloS one, 2013)
Dyskeratosis congenita (DC) is an inherited multisystem disorder of premature aging, cancer predisposition, and bone marrow failure caused by selective exhaustion of highly proliferative cell pools. DC patients also have a poor tolerance to chemo/radiotherapy and bone marrow transplantation. Although critically shortened telomeres and defective telomere maintenance contribute to DC pathology, other mechanisms likely exist. We investigate the link between telomere dysfunction and oxidative and DNA damage response pathways and assess the effects of antioxidants. In vitro studies employed T lymphocytes from DC subjects with a hTERC mutation and age-matched controls. Cells were treated with cytotoxic agents, including Paclitaxel, Etoposide, or ionizing radiation. Apoptosis and reactive oxygen species (ROS) were assessed by flow cytometry, and Western blotting was used to measure expression of DNA damage response (DDR) proteins, including total p53, p53S15, and p21(WAF). N-acetyl-cysteine (NAC), an antioxidant, was used to modulate cell growth and ROS. In stimulated culture, DC lymphocytes displayed a stressed phenotype, characterized by elevated levels of ROS, DDR and apoptotic markers as well as a proliferative defect that was more pronounced after exposure to cytotoxic agents. NAC partially ameliorated the growth disadvantage of DC cells and decreased radiation-induced apoptosis and oxidative stress. These findings suggest that oxidative stress may play a role in the pathogenesis of DC and that pharmacologic intervention to correct this pro-oxidant imbalance may prove useful in the clinical setting, potentially alleviating untoward toxicities associated with current cytotoxic treatments.